Inoculum effect of arbuscular mycorrhizal fungi on soybeans grown in long-term bare-fallowed field with low phosphate availability. Issue 3 (4th May 2018) - Hayashi, Masaki; Niwa, Rieko; Urashima, Yasufumi; Suga, Yuko; Sato, Shusei; Hirakawa, Hideki; Yoshida, Shigenobu; Ezawa, Tatsuhiro; Karasawa, Toshihiko
ABSTRACT: Inoculation with arbuscular mycorrhizal fungi (AMF) can increase the growth of host plants, especially under condition of low phosphate (P) availability. Although this effect is shown relatively easily in simplified systems such as pot experiments, it is often hard to show in the field because of complicating factors such as competition with indigenous AMF. We conducted an AMF inoculation experiment with three Japanese soybean cultivars (Enrei, Misuzudaizu, and Akishirome) in an allophanic (Umbric Silandic) Andosol field under the long-term selective application of major nutrients (NPK and -P) and bare fallow. In the inoculation plots, introduced AMF were well colonized in soybean roots at flowering stage. In the -P plots, inoculation tended to increase the shoot dry weight of all the three soybean cultivars; this effect remained until harvest. Although a significant difference is not recognized, there was a tendency of residual effect on Enrei in the following year. In the NPK plots, inoculation did not significantly increase the shoot dry weight. We thought that in the -P plots, the long-term selective application of N and K and the long-term maintenance of bare fallow created the soil conditions of low P availability and poor native AMF. Thus, introduced AMF can benefit soybean growth and yield in the soil with low competitor AMF density and low phosphate availability.